The Persimmon Borer Sannina uroceriformis Walker, Pest of Persimmon - Russell F. Mizell, III (EDIS)
ENY-835, a 3-page illustrated fact sheet by Russell F. Mizell, describes a wood-boring insect pest of American persimmon, which is used as a root-stock for Oriental persimmon production. Includes references. Published by the UF Department of Entomology and Nematology, July 2006.